0630 Sleep Health of Nursing Staff in an Academic Medical Center: Results of a Survey Study. (12th April 2019) - Christian, Francis; Muppavarapu, Kalyan; Aston, Christopher; Bauer, Chee Yoon; Doshi, Viral
Abstract: Introduction: Nearly 100, 000 deaths are estimated to occur each year in US hospitals attributable to medical errors. Sleep deprivation and disorders have been claimed to be significant contributors. Nurses are at increased risk of sleep deprivation and poor sleep behaviors due to job related factors. However, the prevalence of sleep insufficiency and sleep disorders is not well studied among large cohorts of nurses in the United States.The objective of this study was to survey the sleep habits and to estimate the prevalence of shift work disorder, insomnia, restless leg syndrome, excessive daytime sleepiness and risk factors for obstructive sleep apnea in nurses at an academic medical center. Methods: This was a Cross-sectional institutional adult online survey done at a tertiary care medical center among nurses of age > 18 years. A total of 1165 nurses participated in the survey.The data collected were: demographics, sleep schedule, medications used (to help to sleep, to help to stay wake), medical history of OSA, as well as the STOP-BANG, Epworth sleepiness scale (ESS), insomnia, rest leg syndrome, and shift work disorder questionnaires. Results: Almost half (49%) of respondents averaged less than 7 hours of sleep per night (average sleep time was 6.6 hours) compared to national figures of 28% and 6.8 hours, respectively. Over a quarter (27%) of nurses used medications to assist with sleep, while 13% reported using medications to stay awake. Shift work disorder was found to be prevalent in 31% of all nurses and restless leg syndrome was found in 14%. Chronic insomnia was identified in 31% of all nurses and excessive daytime sleepiness was found in 4.5%. 18.5% of nurses were found to be at moderate-severe risk for Obstructive Sleep Apnea. Conclusion: There is an increased prevalence of insufficient sleep and common sleep disorders amongst nursing staff at our academic medical center. A focus on self-awareness and interventions is warranted to mitigate against the detrimental effects of sleep disorders, ensuring proper safety and performance for nurses at work. Support (If Any): None